Evolution of thermal tolerance and its fitness consequences: parallel and non-parallel responses to urban heat islands across three cities. Issue 1882 (11th July 2018) - Diamond, Sarah E.; Chick, Lacy D.; Perez, Abe; Strickler, Stephanie A.; Martin, Ryan A.
Abstract : The question of parallel evolution—what causes it, and how common it is—has long captured the interest of evolutionary biologists. Widespread urban development over the last century has driven rapid evolutionary responses on contemporary time scales, presenting a unique opportunity to test the predictability and parallelism of evolutionary change. Here we examine urban evolution in an acorn-dwelling ant species, focusing on the urban heat island signal and the ant's tolerance of these altered urban temperature regimes. Using a common-garden experimental design with acorn ant colonies collected from urban and rural populations in three cities and reared under five temperature treatments in the laboratory, we assessed plastic and evolutionary shifts in the heat and cold tolerance of F1 offspring worker ants. In two of three cities, we found evolved losses of cold tolerance, and compression of thermal tolerance breadth. Results for heat tolerance were more complex: in one city, we found evidence of simple evolved shifts in heat tolerance in urban populations, though in another, the difference in urban and rural population heat tolerance depended on laboratory rearing temperature, and only became weakly apparent at the warmest rearing temperatures. The shifts in tolerance appeared to be adaptive, as our analysis of the fitness consequences of warming revealed that while urban populations produced more sexual reproductives under warmer laboratory rearing temperatures, rural populations produced fewer. Patterns of natural selection on thermal tolerances supported our findings of fitness trade-offs and local adaptation across urban and rural acorn ant populations, as selection on thermal tolerance acted in opposite directions between the warmest and coldest rearing temperatures. Our study provides mixed support for parallel evolution of thermal tolerance under urban temperature rise, and, importantly, suggests the promising use of cities to examine parallel and non-parallel evolution on contemporary time scales.